CYP2C19 loss-of-function alleles predicts clinical outcomes in East Asian patients with acute myocardial infarction undergoing percutaneous coronary intervention and stenting receiving clopidogrel - Chen, Yu-Wei; Liao, Yi-Ju; Chang, Wei-Chun; Hsiao, Tzu-Hung; Lin, Ching-Heng; Hsu, Chiann-Yi; Liu, Tsun-Jui; Lee, Wen-Lieng; Chen, Yi-Ming (Frontiers in Cardiovascular Medicine, 2022)
Background CYP2C19 loss-of-function (LOF) alleles reduce the effectiveness of clopidogrel and are associated with high rates of clinical events in patients undergoing percutaneous coronary intervention (PCI) and stenting in Northeast Asians. However, the prevalence and influence of CYP2C19 LOF alleles in Southeast Asians remain unclear. Objectives This study aims to retrospectively investigate the prevalence of CYP2C19 LOF alleles and clinical outcomes in East Asian patients taking clopidogrel and undergoing PCI. Methods Between June 2019 and June 2020, volunteer participants in a single medical center were consecutively selected. The genetic data of CYP2C19 were derived from the Taiwan Precision Medicine Initiative (TPMI). Patients receiving clopidogrel while undergoing PCI with stenting were retrospectively analyzed. Results A total of 999 patients (62.4 ± 11.1 years old, 83.7% men) were enrolled; 39.3% without the CYP2C19 LOF allele (normal metabolizers + rapid metabolizers, NM + RM); 44.9% with one LOF allele (intermediate metabolizers, IM); 15.7% with two LOF alleles (poor metabolizers, PM). The incidence of stroke was higher in the PM subgroup compared to the NM + RM subgroup or IM subgroup in patients presenting with acute myocardial infarction (AMI). The 1-year major adverse cardiac and cerebrovascular events (MACCE)-free survival rates in all participants were similar among the three groups. However, in the AMI group, the 1-year MACCE-free survival rates were significantly lower in the PM subgroup compared to the NM + RM subgroup or IM subgroup. Conclusion In East Asians presenting with AMI, CYP2C19 PM was associated with deleterious cardiovascular outcomes and stroke. Our results reinforce the crucial role of preemptive CYP2C19 genotyping in East Asian AMI patients receiving clopidogrel treatment.